التصميم الانشائي لفندق سياحي في بيت لحم - الزعارير, براء; سعيد, عبد المجيد; ابو سيف, اية (جامعة بوليتكنك فلسطين - مباني, 2020)
تتلخص فكره المشروع في التصميم الانشائي لفندق سياحي في بلدة بيت ساحور قضاء مدينة بيت لحم، بحيث يشمل المشروع كافة التفاصيل اللازمة. ويمثل المشروع دوراً مهما في خدمة السياح في المنطقة بحيث يقع على بعد مسافة 100 م تقريبا من حقل الرعاة الذي يقصده السياح ومناطق اثرية اخرى، كون المنطقة التي سيقام فيها تخلو من الفنادق. يتألف المبنى من سبع طوابق، يحتوي بشكل أساسي على غرف لنزول السياح وكافتيريا بمطبخ ومحلين تجاريين وقاعة اجتماعات كبيرة، بالإضافة الى المرافق الرئيسية التي تجعل المبنى متكامل للخدمة الفعالة من حمامات وادراج ومصاعد. وبسبب وجود خدمات متنوعة تواجدت الحاجة لوجود اختلاف في التصميم لتحقيق الخدمة، فالقاعة مثلا كبيرة سيتم استخدام نوع مختلف من العقدات واستخدام جسور متدلية في أماكن أخرى حسب الحاجة لحاجة وجود مسافات كبيرة فارغة بدون أي عناصر انشائية، وسيتم التصميم بناءا على متطلبات الكود الخرساني الأمريكي (ACI - 318). The idea of the project is summarized in designing the construction of a Hotel in Betsahoor town near Bethlehem city. The project includes all the necessary details. The Importance of this Project is to serve tourist in the area where the hotel is away from Shepherds' Fields around 100 m, beside that Betsahoor town having no any hotels. The building consists of seven floors, basically consist of rooms for tourist, Cafeteria with kitchen, tow stores and bid meeting hole, beside the existence of main facilities that make the building in active service from toilets, stairs and elevators. With existence of different services, the need of making design difference is established, such as the hole and its need for big space there will be use for different kind of slab, and using drop beams for places that needs long spaces without any structural item for example. The design will be based on the needs of American Concrete Institution (ACI -318). from its public library, administration, cafeteria, book fair, as well as a theater for 140 people. The building consists of three blocks. The first block contains the reception space, administration and cafeteria. These blocks at different levels and heights, to be branched into the public library space, theater or exhibition associated with an external corridor. As a result of the large size of the library and the presence of diversity in the form and especially for the existence of a large theater, we will be using a different types of structural elements such as the diversity of slabs and the use of drop beams so that it can carry loads in the long distances between columns, and will be designed based on the requirements of the US concrete code (ACI -318).
CD , no of pages 66 , مباني 6/2020
Keywords: التصاميم الانشائية; ابنية الفنادق